Nash Equilibrium Strategies in Extensive Form Games and Sub Games - C. , Karthi; K. , Selvakumari (International Journal of Psychosocial Rehabilitation, 2020)
Nash Equilibrium solutions are a common solution concept of extensive form games in two-player zero-sum games and bimatrix games. It determines the analysis of subgame-perfect pure and mixed strategy equilibria and the sequential equilibria concept. The main aim of the paper is to investigate the pure and mixed Nash equilibrium strategies of two-person zero-sum games with extensive form games and subgames and provide tools for its systematic study.